Imaging signal transduction in living cells with GFP-based probes. - Zaccolo, M; Pozzan, T (2000)
Since the cloning and the eterologous expression of the Green Fluorescence Protein (GFP), a number of applications have been reported where protein location within the cell or gene expression is revealed by fluorescent imaging of living cells. Modified GFPs, however, can now be exploited not only as a fluorescent reporter but also as a dynamic marker of intracellular signalling events, such as fluctuations in the levels of the second messengers Ca2+ and cAMP, or as a probe for detecting changes in pH in various cell compartments. These genetically manipulated GFPs allow monitoring of the biochemistry of the cell in real time and thus offer the possibility to gain a more precise view of the functioning of live cells.